Political lessons of the medical aspects of the Holocaust through the prism of the evolution of german medicine - I. A. Shikunova; P. P. Shcherbinin (Современная наука и инновации)
The study of the rejection of the moral principles of medical workers and scientists, their societies and academic institutions in favor of a murderous ideology raises fundamental concerns and global implications for the education and practice of current and future medical workers. The worst-case scenario in medicine raises deeply disturbing but important questions here and now: could the Holocaust, one of the greatest evils ever committed against humanity, happen without the complicity of doctors, their societies and the scientific professional community? How did healers become murderers? Could it happen again? The political component of the perception and translation of the lessons and consequences of the Holocaust reflects the clash of universal values, concepts, ideological collisions, including the relations of power and society, the individual and the state, political institutions and everyday practices of individual citizens, political elites and party groups. The source database includes a wide range of historical evidence, including memoirs of witnesses of the Holocaust era, reviews of psychiatrists who were experts at the Nuremberg trials, as well as data from surveys of contemporaries about the political lessons of the Holocaust. The methodological base included the whole complex of historical, social and political approaches, taking into account the methods of the history of everyday life, law, and political issues. The terminology on the problems of the Holocaust was clarified through the prism of medical experiments during the Second World War of 1939-1945. A critical understanding of the historiographical and source-based traditions of the study of the topic "The Holocaust and medicine" in both domestic and foreign scientific communities has been carried out. Obvious deformations of the interpretation of the Holocaust have been revealed in a number of works by American researchers. The assessments of the outstanding psychiatrist Yevgeny Konstantinovich Krasnushkin, who represented the expert community at the Nuremberg trial of Nazi war criminals in 1945, were introduced into scientific circulation. The involvement of memoirs of Holocaust survivors and witnesses of Nazi crimes makes it possible to reconstruct and retransmit amazing pages of survival in the era of Nazism and totalitarianism. The use of private historical methods details the reliable and valuable evidence of atrocities and bullying of concentration camp prisoners under the fascist regime reflected in memoirs, preserved records of contemporaries. The modern medical community, including students, residents of medical universities, are very attentive and sensitive to the consequences of this practice of Nazi Germany, but only if they get acquainted with the medical aspects of the Holocaust during their studies. It is concluded that the Nazi racial laws were mastered, and quite successfully justified not only by the luminaries of German medicine, but often by ordinary representatives of the medical community, which often turned doctors into accomplices in criminal activities during the reign of Hitler. It is proved that memorializing the historical memory of the Holocaust tragedy, including through the prism of medical experiments on people, can hinder the development of neo-Nazi views, nationalism and extremism, antiSemitism and xenophobia in modern society. The political aspects of studying the problem of the Holocaust in modern Russia are convincingly detailed, which reflects the urgent sociopsychological, everyday, ethno-confessional needs of the development of the population of the Russian Federation, including civil society and public initiatives for the formation of tolerance, respect for human rights and ethnic integrity, and identity.